[All]‐S, S‐dioxide Oligo‐Thienylenevinylenes: Synthesis and Structural/Electronic Shapes from Their Molecular Force Fields. Issue 2 (11th December 2018) - Aharon, Cheryl; Guijarro, Fernando G.; Medina Rivero, Samara; Ramírez, Francisco J.; Caballero, Rubén; Casado, Juan; Langa, Fernando; Rozen, Shlomo
Abstract: Oligo‐ S, S ‐dioxothienylenevinylenes have been prepared by transferring oxygen atoms to the sulfur atoms using the HOF⋅ CH3 CN complex. Their photophysical properties are presented in comparison with their thiophenevinylene congeners. Together with their vibrational properties and molecular force fields, this study allows for the interpretation of the alteration of aromaticity and inter‐ring exocyclic π‐conjugation in this series. Abstract : Selective oxidation of the sulfur atoms of oligothiophene vinylene oligomers, which leaves the surrounding electron‐rich olefins intact, promotes the enhancement of inter‐ring/ exocyclic π‐conjugation such as demonstrated by the analysis of the molecular force fields (i.e., force constants) associated to the C=C and C−C bonds.